(untitled) (Eurasian Journal of Engineering and Technology, 2023)
The research teams have a variety of reasons for wanting to find suitable solutions to the problem of global warming. When certain alumino-silicates materials, such as metakaoline, fly ash, slag and rice husk ash are alkali activated, the resulting principal binder is what is known as geopolymer concrete. Commonly, geopolymer concrete has mechanical strength characteristics like conventional concrete. Repairing RC beams refers to the actions that can be done in order to recover the inherent structural behavior before failure. This study was devoted to examine possibility of using side flange strips technique that made by fiber reinforced polymers to repair pre-failed I – section reinforced geopolymer beams. Both Glass and Carbon fiber reinforced polymer strips were used and compared. The outcomes illustrated that the proposed technique was able to recover the service load and the maximum load. The stiffness levels was increased after rehabilitation for both glass and carbon fiber. The initial cracking load occurrence was changed in nature from the tension to compression zone after repairing